Chaluce. Od obietnicy ziemi do Ziemi Obiecanej - Ulanowski, Krzysztof (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2011)
Genesis of the He Halutz movement comes from a complicated mosaic of the Jewish ideas of the late nineteenth and twentieth century of the national and the socialist character. The idea from which the Halutzim originated has its roots in both the utopia and the purely pragmatic intentions. An important element for understanding the history of the movement in general is the observation of the evolution of the global concept of a similar character and relating them to the situation on Polish territories and in Poland after 1918. This issue involves the attitude towards the Halutzim in these countries in which the movement was organized and was developed. The most important question concerning the operation is: who was the patron, who was the owner of the land on which farms were created and who employed them in factories? This matter is connected with the reaction of the Polish state authorities and ordinary users of the land and later the Nazis after 1939. The study of organizing the movement from the inside is reduced to analysis of ways in which they were working before and during the war. One could not overlook the significant contribution of the Halutzim in the Jewish resistance in the Warsaw Ghetto uprising. A detailed examination shows great distribution of He Halutz movement on the Polish territory and surprisingly little awareness of this fact. In the Polish sources and modern historical research one can find only marginal information about the movement and for this reason a big difficulty for a researcher with the verification of the results of the study. Therefore, I focus on the presentation of the best documented examples of places (Czortków, Grodno, Warszawa) and pioneers who make up the movement. In the final stage I am trying to define the role that the movement played in creating the Kibbutz movement and in the process of building an independent state of Israel.